Weekly enzyme replacement therapy may slow decline of renal function in patients with Fabry disease who are on long-term biweekly dosing - Schiffmann, Raphael; Ries, Markus (Journal of the American Society of Nephrology, 2007)
This study was performed to determine whether adult male patients with Fabry disease who demonstrate a continuing decline in renal function despite 2 to 4 yr of conventionally dosed agalsidase alfa therapy (0.2 mg/kg every other week [EOW]) show an improved slope of decline with weekly administration using the same dosage. Eleven (27%) of 41 adult male patients with Fabry disease who participated in long-term agalsidase alfa clinical trials and who had demonstrated a slope of decline in estimated GFR (eGFR) of ≥5 ml/min per 1.73 m2/yr while receiving long-term treatment with agalsidase alfa at the currently recommended dosage of 0.2 mg/kg, infused EOW, were enrolled in this open-label, prospective study. Patients were switched from EOW to weekly infusions and followed for an additional 24 mo. Before switching to weekly dosing, eGFR was 53.7 ± 6.3 ml/min per 1.73 m2 (mean ± SEM), and mean rate of change in eGFR was −8.0 ± 0.8 ml/min per 1.73 m2/yr. During the 24-mo follow-up period after switching to weekly dosing, the mean rate of change in eGFR was observed to slow to −3.3 ± 1.4 ml/min/1.73 m2/yr (P = 0.01 versus EOW). After switching to weekly dosing, three patients demonstrated an improvement in eGFR and six patients demonstrated a slowing in the rate of eGFR decline; only two patients failed to improve their eGFR slope. A multiple regression model confirmed that the weekly infusion regimen was the strongest explanatory variable for the change in eGFR (P = 0.0008), with a weaker contribution from the concomitant use of angiotensin converting enzyme inhibitors/angiotensin receptor blockers (P = 0.02). These results suggest that weekly infusions of agalsidase alfa at a dosage of 0.2 mg/kg may be beneficial in the subgroup of patients who have Fabry disease and whose kidney function continues to decline after 2 to 4 yr or more of standard EOW dosing.